Answer:
x = 1
y = 2
z = 3
Explanation:
3x + 2y + z = 10 | ×3 |
9x - 6y + z = 0 | ×1 |
9x + 6y + 3z = 30
9x - 6y + z = 0
_______________--
12y + 2z = 30..... (4)
3x + 2y + z = 10 | ×1 |
x - y - 3z = -10 | ×3 |
3x + 2y + z = 10
3x - 3y - 9z = -30
_______________--
5y + 10z = 40........ (5)
4 and 5
12y + 2z = 30 | ×5 |
5y + 10z = 40 | ×1 |
60y + 10z = 150
5y + 10z = 40
_____________--
55y = 110
y = 110/55
y = 2
5y + 10z = 40
5(2) + 10z = 40
10 + 10z = 40
10z = 40 - 10
10z = 30
z = 30/10
z = 3
x - y - 3z = -10
x - 2 - 3(3) = -10
x - 2 - 9 = -10
x - 11 = -10
x = -10 + 11
x = 1